PENGARUH BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR DAUN KELOR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) - Widyarti, Ni Made Pita; Tambing, Yohanis (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
Cucumber, an economically valuable horticultural product, requires enhanced productivity and quality. This study aimed to investigate the influence of different concentrations of liquid organic fertilizer (LOF) of Moringa leaf on the growth and yields of cucumber plants. The research was conducted at the Academic Garden of the Faculty of Agriculture, Tadulako University, Palu, between November 2020 and January 2021. Employing a randomized block design (RBD), the experiment involved five levels of Moringa leaf LOF concentrations: Control (P0), 100 ml/l water (P1), 200 ml/l water (P2), 300 ml/l water (P3), and 400 ml/l water (P4). The findings revealed a significant effect of Moringa leaf LOF concentration on the growth and yield components of cucumber plants. The concentration of 300 ml/l water of Moringa leaf LOF resulted in taller plants, an increased leaf area size and number and a higher fruit number.